Myopia Control With Multifocal Lens in School-Aged Children: A Meta-Analysis - Chen, Meilan; Xu, Lu; Li, Hongyang; Cai, Fengping; Wang, Hao; Hu, Chun; Wu, Yi (Frontiers in Pediatrics, 2022)
Background: Myopia is one of the most common eye diseases in school-aged children. Multifocal lens (MFL) is one of the interventions that has being widely applied to control the progress of myopia. However, the treatment effects of MFLs in school-aged children require to be systematically evaluated. Methods: A systematically analysis on qualified randomized controlled trials (RCTs) where MFLs were prescribed as the intervention and single-vision lenses (SVLs) as the control was conducted. Treatment effects referring to the mean differences in spherical equivalent refraction (SER) and axial length (AL) between MFLs and SVLs groups were analyzed. Results: With annual visit (3 years follow up), the weighted mean differences (WMDs) in SER between MFLs and SVLs were 0.29 D (95% CI, 0.21 0.37, p<0.00001), 0.46 D (95% CI, 0.32 0.60, p<0.00001) and 0.64 D (95% CI, 0.40 0.88, p<0.00001) at the first, second and third year; in AL were -0.12 mm (95% CI, -0.14 -0.11, p<0.00001), -0.19 mm (95% CI, -0.22 -0.16, p<0.00001) and -0.26 mm (95% CI, -0.31 -0.21, p<0.00001) at the first, second and third year. With 6-month interval trials (2 years follow up), the WMDs in SER from MFLs were 0.14 D (95% CI, 0.08 0.20, p<0.0001), 0.19 D (95% CI, 0.11 0.28, p<0.0001), 0.24 D (95% CI, 0.16 0.33, p<0.0001), 0.31 D (95% CI, 0.18 0.44, p<0.0001) and in AL from MFLs were -0.08 mm (95% CI, -0.09 -0.07, p<0.00001), -0.10 mm (95% CI, -0.12 -0.09, p<0.00001), -0.14 mm (95% CI, -0.17 -0.11, p<0.00001), and -0.18 mm (95% CI, -0.22 -0.14, p<0.00001) slower comparing with SVLs at follow up of 6-month, 12-month, 18-month and 24-month, respectively. Conclusion: The treatment effects of MFLs to slow down the myopic progress are positive in both 6-month and annual visit trials and which could be sustained to 36 months. While a slight weaker treatment effect was observed after the first visit in 6-month visit, a slight rebound was observed at following visit points. Furthermore, the treatment effects in annual visit are more profound than 6-month visit at almost all stages especially in SER. Our analysis encourages the MFLs users to maintain a long-term treatment with annual visit.